PREVENTION OF CHRONIC PYELONEPHRITIS AND ITS IMPACT ON HEALTH - Nargiza Eshonqulova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Chronic pyelonephritis (CP) is an infection of the renal parenchyma that is usually associated with systemic signs of inflammation, since the presence of fever is usually an indicator of renal damage. The kidneys and urinary tract are usually free of germs. Most cases of CP result from passage of fecal-derived organisms through the urethra and periurethral tissues into the bladder with subsequent invasion of the kidney. Normally, urine drainage prevents infection by washing away bacteria that enter the urinary tract.